Możliwości rozwoju magazynów energii w Polsce w perspektywie długoterminowej - Augustyn, Aleksandra; Mirowski, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The EU climate policy assumes an increase of the renewable energy share in total energy generation to 27% by 2030 year. This step is a response to the climate change, based on the fact that the operation of renewable energy power plants is emission-free. However, it is important to note that electricity generation from renewable sources, mainly wind and photovoltaic, is highly dependent on atmospheric conditions, and is thus unreliable. As a consequence, the development of stable energy sources is required in order to guarantee energy security. Promising solutions include energy storage technologies. The power-to-gas systems may be deployed as adjuncts to wind parks or photovoltaic generation. The energy generated at the time of maximum sunshine or wind is accumulated and used at the moment of high electricity demand. The purpose of this article is to propose a location for the development of the Power-to-gas technology in Poland aiming to store energy derived from renewable energy sources.
The possibilities of energy storage development in Poland from a long-term perspective
Keywords: renewable energy sources; energy storage; power to gas